Tuerie de l'École Polytechnique avec Mélissa Blais (P.U. #24) (2012)
Mélissa Blais est doctorante en sociologie à l'UQAM. Militante féministe et professionnelle de recherche à l'IREF, elle a étudié les réceptions du discours féministe à la suite de la tuerie de l'École Polytechnique de Montréal le 6 décembre 1989. Selon ce qu'on lit dans son livre, l'état psychologique de Marc Lépine était loin d'être la clé qui permet de comprendre les 14 meurtres qu'il a commis cette journée-là. Son geste était un message politique : mort au féminisme. La planification et la volonté derrière l'acte sont du registre de l'attentat. L'entrevue de la fin, pour commencer un livre. Janick Bastien Charlebois est professeure de sociologie à l'UQAM. Dans La virilité en jeu (Septentrion, 2011), elle souligne que de parler uniquement d'homophobie tend à nier la dimension culturelle de la discrimination dont sont victimes les jeunes gais. Les problèmes d'intégration des homosexuels ne sont pas qu'une question d'attitude individuelle, ils sont aussi le fruit d'un hétérosexisme dispersé dans la réalité sociale.
Keywords: 1900-1999; 1980-1989; amériques; antiféminisme; approches et analyses; hétérosexisme; identités LGBTQIA2+; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques; violences

Contested psychiatric ontology and feminist critique: ‘Female Sexual Dysfunction’ and the Diagnostic and Statistical Manual - Angel, Katherine (History of the Human Sciences, 2012)
In this article I discuss the emergence of Female Sexual Dysfunction (FSD) within American psychiatry and beyond in the postwar period, setting out what I believe to be important and suggestive questions neglected in existing scholarship. Tracing the nomenclature within successive editions of the American Psychiatric Association’s Diagnostic and Statistical Manual (DSM), I consider the reification of the term ‘FSD’, and the activism and scholarship that the rise of the category has occasioned. I suggest that analysis of FSD benefits from scrutiny of a wider range of sources (especially since the popular and scientific cross-pollinate). I explore the multiplicity of FSD that emerges when one examines this wider range, but I also underscore a reinscribing of anxieties about psychogenic aetiologies. I then argue that what makes the FSD case additionally interesting, over and above other conditions with a contested status, is the historically complex relationship between psychiatry and feminism that is at work in contemporary debates. I suggest that existing literature on FSD has not yet posed some of the most important and salient questions at stake in writing about women’s sexual problems in this period, and can only do this when the relationship between ‘second-wave’ feminism, ‘post-feminism’, psychiatry and psychoanalysis becomes part of the terrain to be analysed, rather than the medium through which analysis is conducted.
Number: 4
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; europe; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Y a-t-il un « cycle de la violence antiféministe »?: Les effets de l’antiféminisme selon les féministes québécoises - Blais, Mélissa (Recherches féministes, 2012)
S’appuyant sur la recherche Les attaques antiféministes, menée en partenariat avec L’R des centres de femmes du Québec, l’auteure documente les actions antiféministes et analyse leurs effets sur le mouvement féministe québécois. Inspirée par l’hypothèse de L’R des centres de femmes, selon laquelle les féministes réagissent à la violence antiféministe comme les femmes violentées en contexte conjugal et postconjugal, l’auteure se demande s’il existe un « cycle de la violence antiféministe ». À l’aide de la théorie du « cycle de la violence conjugale » et des études féministes sur les violences masculines contre les femmes, elle observe les similitudes entre les effets de la violence conjugale et les effets de la violence antiféministe, mais aussi les limites de l’analogie inhérentes aux dimensions collectives des attaques antiféministes.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; antiféminisme; approches et analyses; canada; cours; discipline; histoire et politique; pol4102; pol5185; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; violences

Choral, public and private listener responses to Hildegard Westerkamp's École Polytechnique - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; DIG; amériques; arts; canada; cyborg; deuil; discipline; femmes* artistes; guérison; musique; mémoire; polytechnique; périodes historiques; ressource en ligne; régions géographiques; thématiques; trauma; violences; violences contre les femmes*; violences sexistes; émotions